The Sisterhood and Liberation: Representation of Hui’an Women in Film and Their Socio-Cultural Contexts - Lin, Maner; Sriruksa, Arunee; Teawkul, Papitchaya (Journal of Ecohumanism, 2025)
This study analyzed three films depicting Hui'an women from different historical contexts, exploring how these films portray sisterhood and the ways in which these portrayals intersect with local social cultures and national politics to advance female emancipation. The sisterhood formed by female characters in response to the pressures of traditional social and cultural discipline includes: the labor community transitioning from the "family" to the "society"; the "same-sex relationships" that result from the extreme evolution of the alliance of disadvantaged women; the emotional, spiritual community that transcends familial bonds. The formation and maintenance of sisterhood among Hui'an women are deeply linked to regional cultural characteristics and historical conditions, and to varying degrees, they challenge societal norms and restrictions imposed on women. This defiance and deconstruction present a rebellious stance, playing an indispensable role in the awakening of self-awareness and the liberation process of marginalized female groups.